The Impact of ESG Disclosure on Market Reaction: Sustainability Perspective in the Banking Sector - I Kadek Jonh Stiawan (International Journal of Economics Accounting and Management, 2026)
This study aims to assess the sustainability aspects of banking companies and their impact on market response. Corporate sustainability is measured through ESG disclosure, encompassing environmental, social, and governance dimensions. The study was conducted on banking companies listed on the Indonesia Stock Exchange during the 2020–2023 period, with a population of 47 companies. The sample was selected using purposive sampling, resulting in 8 companies observed over 4 years, yielding a total of 32 units of analysis. Data were collected through documentation methods from secondary sources and analyzed using multiple linear regression with the assistance of STATA software. The results indicate that ESG disclosure does not have a significant effect on market response. This condition is likely due to investors’ greater focus on financial fundamentals and macroeconomic conditions, while ESG disclosure is still perceived as a regulatory formality with limited credibility and relevance in investment decision-making.